The Creative Activity of National Intelligencia in the Creation of Kazakh Terminology - Mazhitayeva, Sh.; Rapisheva, Zh.; Kagazbayev, Zh.; Toleubayeva, K.; Zhumagulov, A.; Zhumagulov, S.; Smagulova, N. (Published by Canadian Center of Science and Education, 2015)
The issues relating to the creating, formation, systematizing and putting in good order the terminology as a phenomenon is of vital importance for full-blended functioning of the Kazakh language in various fields of science. The present article focuses on the studying of factures that display the formation of scientific style and terminology at the beginning of XX century. It also emphasizes the rule of translation, first course book, and the usage of terms; characteristic features of scientific style, their special nature stage of formation and their development peculiarities. The study of Kazakh progressive-mind scholars’ heritage who unsparingly contributed the functioning of the Kazakh language in science is very significant both for science and society. Keywords: term, the use of terms, terminology, scientific terminology, scientific style, scientific language
Keywords: term; the use of terms; terminology; scientific terminology; scientific style; scientific language; Kazakh intelligentsia; the first course books